VD_FINDINFO Jug / 2025 / 406 vom 10. Februar 2025 - VD Tribunal cantonal (2025)
INDEMNITÉEN GÉNÉRAL, TORT MORAL, DOMMAGE PUREMENT ÉCONOMIQUE, AVOCAT | 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH)